PENERAPAN STRATEGI ORGANISASI DALAM PENYUSUNAN RENCANA STRATEGIS: SEBUAH PERSPEKTIF FRED R. DAVID - Muharam, Suhari; Nur Afni, Rizky; Fitria, Ni’mah; Burhanuddin, Burhanuddin (J-MIND (Jurnal Manajemen Indonesia), 2025)
This study aims to examine the implementation of organizational strategies in strategic planning according to Fred R. David's perspective, which divides strategies into three main categories: integration, intensification, and diversification. This study applies a literature review method by examining various theoretical sources and previous research findings related to organizational strategy planning and implementation. The research data includes academic literature and strategic management books. The results indicate that the success of formulating strategic plans is highly dependent on selecting the appropriate type of strategy in accordance with the internal and external situations of the organization. Additionally, the success of strategy implementation is influenced by the clarity of programs, resource allocation, and stakeholder participation.